The Influence of the Quantity of Corporate Social Responsibility and National Diversity of the Board of Companies on Corporate Value with the Availability of Sustainability Reports as a Moderating Variable - Sameer Seth (Greenation International Journal of Economics and Accounting, 2023)
This study aims to analyze the influence of corporate social responsibility and diversity of corporate board nationalities on firm value. The data used is secondary data sourced from annual reports and Thomson Reuters Data Stream. The data analysis technique used in this test is multiple regression analysis. The results of the regression analysis show that CSR spending, the proportion of foreign commissioners, and the proportion of foreign directors have no effect on firm value. The results of the regression analysis also show that disclosure of sustainability reports has no influence in moderating the relationship between CSR spending and firm value. Meanwhile, disclosure of sustainability reports has a negative moderating effect on the relationship between the proportion of foreign commissioners and company value, and has a positive effect on the relationship between the proportion of foreign directors and company value.